Eliminating Ecological Damage in Geothermal Energy Extraction: Fulfillment of Ecological Rights by Proposing Permits Standardization - Hanum, Willy Naresta; Ha , Tran Thi Dieu; Firmandayu, Nilam (CV. Ius et Ambientis, 2024)
The rights of living things and inanimate objects in an ecological unity must be fulfilled in a balanced and fair manner. However, the shift in licensing arrangements to approve geothermal utilization in conservation forest areas has degraded the power of supervision. Likewise, the non-rigidity of the standardization of geothermal permit criteria has also resulted in the utilization of geothermal energy not being by the principles of ecological justice. This study is a normative study that uses a legislative approach by analyzing legal materials. The regulations used relate to geothermal regulations and licensing. The main theories used for the analysis are ecological justice and the triangle of energy. This study shows that, first, the issuance of geothermal permits should be strengthened by returning the requirements for approval of forest area utilization and environmental approval to remain in the form of permits to provide legal force for supervision and control of geothermal impacts in forest areas and the environment in general. Second, geothermal utilization permits in conservation forest areas need to be standardized. This study recommends changes to geothermal regulations that adopt the values of ecological justice, which are fair to humans and non-humans. Geothermal utilization must be supported to carry out the energy transition, but guarantees of rights for non-humans in ecosystem units must be given proportionally. Non-humans must not suffer losses due to the tendency of natural resource utilization, which only benefits the economic aspect of humans.